GENETIC RISK FACTORS IN ACUTE CENTRAL SEROUS CHORIORETINOPATHY. Issue 12 (December 2019) - Mohabati, Danial; Schellevis, Rosa L.; van Dijk, Elon H. C.; Altay, Lebriz; Fauser, Sascha; Hoyng, Carel B.; De Jong, Eiko K.; Boon, Camiel J. F.; Yzer, Suzanne
Abstract : Purpose: To investigate genetic associations in white patients with acute central serous chorioretinopathy (aCSC) and to assess genetic differences between aCSC and chronic CSC (cCSC). Methods: A total of 135 aCSC patients, 272 cCSC patients, and 1, 385 control individuals were included. Eight single nucleotide polymorphisms were genotyped for ARMS2 (rs10490924), CFH (rs800292, rs1061170, rs1065489, rs1329428, rs2284664, rs3753394), and NR3C2 (rs2070951). Also, C4B gene copy numbers were analyzed. Results: Three single nucleotide polymorphisms in the CFH gene were significantly associated with aCSC: rs800292 ( P = 0.003, odds ratio = 1.53 [95% confidence interval = 1.15–2.03]), rs1061170 ( P = 0.002, odds ratio = 0.64 [95% confidence interval = 0.48–0.86]), and rs1329428 ( P = 5.87 × 10 −6, odds ratio = 1.83 [95% confidence interval = 1.40–2.38]). A significant difference was found in the distribution of C4B gene copy numbers in aCSC patients compared with controls ( P = 0.0042). No differences could be found among the selected variants between aCSC and cCSC patients. Conclusion: Three variants in the CFH gene and copy number variations in C4B were found to be significantly associated with the risk of aCSC development. Despite the differences in clinical presentation, acute and chronic CSC may share a similar genetic predisposition based on our present analysis. Other genetic and/or nongenetic risk factors may be more influential in the differentiation toward an acute or a chronic phenotype of CSC. Abstract : Supplemental Digital Content is Available in the Text.Three variants in the CFH gene and copy numbers of C4B were found to be significantly associated with the risk of acute central serous chorioretinopathy in whites. Acute and chronic central serous chorioretinopathy may share a similar genetic predisposition based on the tested genetic variants in ARMS2, CFH, and NR3C2 genes, and copy numbers of the C4B gene.